Land Suitability Analysis for Peanut (Arachis hypogea) Farming in World Heritage Conservation Area Sangiran - Agung Rimayanto Gintu; Bistok H Simanjuntak; Suprihati Suprihati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Sangiran Archaeological Site was conservation area protected by national and inter-national regulations. Sangiran Site, however, was an open site inhabited by people commonly working as farmer cultivating food crops and horticulture. During dry season, most farmers generally cultivate peanut. This study aims to determine the suitability of land in the Sangiran area for peanut cultivation. The study was conducted by analyzing soil samples taken from several locations at the Sangiran site: Blue Clay and Black Clay from the Pucangan formation in Pablengan Village, and Kabuh soil from around the Sangiran Triangulation Monument. The results from 3 sampling areas showed that the score of Black Clay area 2.13 mean "unhealthy soil" for peanut farming. The Blue Clay area showed the score about 1.87 also mean that "unhealthy soil" for peanut farming. Kabuh formation area showed the score about 2.97 mean that "marginal health" for peanut farming. Overall the score of Sangiran areas mean that the soil belongs to "very bad" quality for peanut cultivation.